LATIN LEGAL TERMINOLOGY IN ESTONIA - RISTIKIVI, Merike (Comparative Legilinguistics, 2009)
The article examines the use of Latin in contemporary legal texts and its impact on terminology. The terminology analysed in the article comprises the terms collected from the Estonian juridical periodicals. Attention is paid to the following topics: average size of the vocabulary of the Estonian lawyer; the most frequent Latin terms and phrases; context of Latin terms and phrases; main problems and errors in the use of Latin.